Risk of adverse events in psoriasis patients receiving classic systemic drugs and biologics in a 5‐year observational study of clinical practice: 2008–2013 results of the Biobadaderm registry. (31st March 2014) - Carretero, G.; Ferrandiz, C.; Dauden, E.; Vanaclocha Sebastián, F.; Gómez‐García, F.J.; Herrera‐Ceballos, E.; De la Cueva‐Dobao, P.; Belinchón, I.; Sánchez‐Carazo, J.L.; Alsina‐Gibert, M.; López‐Estebaranz, J.L.; Ferrán, M.; et al.
Abstract Background Biobadaderm is the Spanish registry of psoriasis patients receiving systemic treatment in clinical practice. Objective To compare the safety of biologics and classic systemic treatment. Methods Prospective cohort of patients receiving biologics and classic systemic therapies between 2008 and 2013 in 12 hospitals are included. We registered demographic data, diagnoses, comorbidities, treatments and adverse events (AE). We obtained raw relative risks (RR) for specific AE. Multivariate analysis consisted of Cox models adjusting for age, gender, chronic hepatic disease and previous cancer. Results A total of 1030 patients received biologics (2061 AE in 3681 person‐years), 926 patients classic systemic drugs (1015 AE in 1517 person‐years). Ninety‐three per cent of AE in both groups were non‐serious, 6% serious and 0.003% fatal. The age‐ and gender‐adjusted hazard ratio of AE was lower in the biologics group [hazard ratio 0.6 (95% CI: 0.5–0.7)].We found no differences in rates of serious and mortal AE. Some system organ class AE rates differed between both groups. As limitations: Prescription bias might affect the incidence of AE in both groups. Association of drug and AE was based on timing: associations might not be causal. Conclusion Patients receiving biologics had lower risk of AE. We did not find differences in the risk of serious or fatal AE.